Effect of Rhizophora apiculata bark extract on SGOT levels in Rattus norvegicus induced by dexamethasone - Sampurna, William Wijaya; Handajani, Fitri; Rasyida, Annisa Ullya; Nandaka, I Ketut Tirka (Universitas Wijaya Kusuma Surabaya, 2025)
Background: The liver's presence of fat has a histological picture with lipids>5%, and no secondary cause is called NAFLD. Rhizophora apiculata can serve as a therapeutic or prophylactic agent in NAFLD due to its flavonoid content. Objective: to ascertain the impact of Rhizophora apiculata extract administration on SGOT levels in white rats subjected to dexamethasone induction. Methods: The experimental animals were categorized into four groups: K- group, no treatment; K+ group, which was administered dexamethasone at a dosage of 5 mg/kg BW from the 15th to the 21st day; KP1 group, which received Rhizophora apiculata ethanol extract at a dosage of 56 mg/kg BW from the 8th to the 21st day, along with dexamethasone at 5 mg/kg BW from the 15th to the 21st day; and KP2 group, which was given Rhizophora apiculata ethanol extract at 56 mg/kg BW and dexamethasone at 5 mg/kg BW from the 15th to the 21st day. Result: The data were not normally distributed (p < 0.05), so the Kruskal-Wallis test was carried out, which yielded p < 0.05. Consequently, the post hoc test was continued, namely the Mann-Whitney U test. The post hoc test of the K-group and K+ obtained p < 0.05. The K+ group and KP1 and KP2 showed P > 0.05, indicating no significant difference. Conclusion: The Rhizophora apiculata extract at a dose of 56 mg/kg BW for 7 days can reduce SGOT levels in the Kp2 group.